Neurostimulation of the gastrointestinal tract in children: is it time to shock the gut?. Issue 5 (October 2016) - Lu, Peter L.; Di Lorenzo, Carlo
Abstract : Purpose of review: The use of neurostimulation for treatment of gastrointestinal disorders has been growing over the past two to three decades. Our objective is to review current applications of neurostimulation in the treatment of gastrointestinal disorders with an emphasis on the use of these treatment modalities in children. Recent findings: Gastric electrical stimulation can lead to symptomatic improvement in children with chronic nausea and vomiting refractory to conventional treatment, and a recent report of long-term outcomes is encouraging. Sacral nerve stimulation can be effective in the treatment of children with constipation and fecal incontinence refractory to conventional treatment, and patient satisfaction with treatment remains high despite the risk of complications requiring further surgery. Abdominal transcutaneous electrical stimulation and posterior tibial nerve stimulation are noninvasive neurostimulation techniques that may be effective in the treatment of children with constipation and fecal incontinence. Summary: Although neurostimulation-based treatments appear promising and offer advantages compared to more invasive surgical treatment options, evidence for their benefit in children remains limited. High-quality studies demonstrating safety and efficacy and a better understanding of the mechanism of each modality are needed before there is more widespread acceptance of neurostimulation in the treatment of children with gastrointestinal disorders.